Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\left(x+7\right)\left(3x-1\right)=x^2-49\)
\(\left(x+7\right)\left(3x-1\right)-\left(x+7\right)\left(x-7\right)=0\)
\(\left(x+7\right)\left(3x-1-x+7\right)=0\)
\(\left(x+7\right)\left(2x+6\right)=0\)
\(\hept{\begin{cases}x+7=0\\2x+6=0\end{cases}}\)
\(\hept{\begin{cases}x=-7\\x=-3\end{cases}}\)
\(b,5\left(x-3\right)-4=2\left(x-1\right)+7\)
\(5x-15-4=2x-2+7\)
\(5x-19=2x+5\)
\(3x=24\)
\(x=8\)
a)4×(x-5)-(x-1)×(4x-3)=5
=>4x-20-4x2+7x-3-5=0
=>-4x2+11x-28=0
=>-4(x2-\(\frac{11x}{4}\)+7)=0
=>\(-4\left(x-\frac{11}{8}\right)^2-\frac{327}{16}< 0\)
=>vô nghiệm
b) (3x-4)(x-2)=3x(x-9)-3
=>3x2-10x+8=3x2-27x-3
=>17x=-11
=>x=-11/17
c)(x-5)×(x-4)-(x+1)×(x-2)=7
=>x2-9x+20-x2+x+2=7
=>22-8x=7
=>-8x=-15
=>x=8/15
1
a) \(\left(3x+1\right)\left(3x-1\right)=9x^2-1\)
\(\left(x+5y\right)\left(x-5y\right)=x^2-25y\)
b) \(\left(x-3\right)\left(x^2+3x+9\right)=x^3-27\)
\(\left(x-5\right)\left(x^2+5x+25\right)=x^3-125\)
Bài 3:
a: \(\Leftrightarrow x^2+8x+16-x^2+1=16\)
=>8x+1=0
=>x=-1/8
b: \(\Leftrightarrow4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
=>2x+255=0
=>x=-255/2
c: \(\Leftrightarrow x^3-6x^2+12x-8-x^3+64+6x^2+12x+6=49\)
=>24x+62=49
=>24x=-13
=>x=-13/24
d: =>x^3+8-x^3-2x=15
=>-2x=15-8=7
=>x=-7/2
a)
\(\left(3x^2-x+1\right)\left(x-1\right)+x^2\left(4-3x\right)=\frac{5}{2}\)
\(\Leftrightarrow3x^3-x^2+x-3x^2+x-1+4x^2-3x^3=\frac{5}{2}\)
\(\Leftrightarrow2x-1=\frac{5}{2}\Leftrightarrow2x=1+\frac{5}{2}=\frac{7}{2}\Leftrightarrow x=\frac{7}{4}\)
b)
\(4\left(x+1\right)^2+\left(2x-1\right)^2-8\left(x-1\right)\left(x+1\right)=11\)
\(\Leftrightarrow4\left(x^2+2x+1\right)+\left(4x^2-4x+1\right)-8\left(x^2-1\right)=11\)
\(\Leftrightarrow4x^2+8x+4+4x^2-4x+1-8x^2+8=11\)
\(\Leftrightarrow8x+4-4x+1+8=11\Leftrightarrow4x+13=11\Leftrightarrow4x=-2\Leftrightarrow x=-\frac{1}{2}\)
c)
\(\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)
\(\Leftrightarrow4x^2-4x+1+x^2+6x+9-5\left(x^2-7^2\right)=0\)
\(\Leftrightarrow4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
\(\Leftrightarrow-4x+1+6x+9+245=0\Leftrightarrow2x+255=0\Leftrightarrow x=-\frac{255}{2}\).
a ) ( 3x2 - x + 1 ) ( x + 1 ) + x2 ( 4 - 3x ) = 5/2
=> 3x3 + 3x2 - x2 - x + x + 1 + 4x2 - 3x3 = 5/2
=> 6x2 + 1 = 5/2
=> 6x2 = 1,5
=> x2 = 0,25
=> x = 0,5